Design and implementation of an EPC Class-1 Generation-2 UHF Frid Sniffer on software-defined radio - Macalino, Sophia Martina D. (2010)
The software-defined radio (SDR) is an emerging technology that is expected to offer better solutions to future RF design challenges. It promises increased performance and advanced computing capability due to its flexibility and ease of adaptation. Such properties of the SDR allow easy reconfiguration and reprogramming by software, support of multiple protocols and services, and high performance signal processing. It is predicted that SDR systems will support multi-standards architecture and design challenges for a wide variety of radio applications, particularly in digital communications. One of the applications of the SDR is the design and implementation of radio frequency identification (RFID) readers. All RFID readers and tags follow a strict set of rules called the protocol. Different protocols define different frequencies of operation, data rate, modulation schemes, encoding schemes, and others depending on the type and application of the RFID system used. The specifications set by the protocol can be programmed on an SDR. The project is the design and implementation of a device called the sniffer that will analyze transmission data between a single RFID reader and tag in real-time using the EPC Class-1 Generation-2 UHF RFID protocol (also known as the ISO/IEC 18000-6C). Much of the sniffer's design will be based on that of an RFID receiver. The device will operate by demodulating and interpreting the signals coming from the reader and tag during the interrogation round. Implementation of the proposed project will be on a software-defined radio composed of an analog RF front end for signal acquisition and FPGA development platform for digital signal processing. The sniffer will output the tag transition states, commands transmitted by the reader, and the link timing specified by the EPC Class-1 Generation-2 UHF RFID protocol. All the output will be displayed on a host computer. The proposed project's performance will be tested with a UHF RFID reader and tag following the EPC Class-1 Generation-2 UHF RFID protocol. The development of this project is an incremental step towards the development of an SDR-based fully-functional RFID reader. Future research may focus on the inclusion of additional features such as the transmitter part, support for other RFID protocols, and support for other services.
Thesis (B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman
Keywords: Software radio; Electric network analyzers -- Design and construction; Radio frequency identification systems; Sniffer; EPC Class-1 Generation-2 UHF RFID Frid Sniffer; EPC Class-1 Generation-2 UHF RFID protocol